(untitled) (International Journal of Geoscience, Engineering and Technology, 2021)
The objective of this study was to identify and classify geological and environmental risk areas in the city of Itambacuri - MG. It was realized that the city was developed in a natural flood basin region of the Itambacuri River and Engenho and Fortuna streams, which cross the city of Itambacuri. The geological formation is characterized principally by alluvial soils. The survey consisted of going through neighborhoods and observing the characteristics of slopes and signs of carriage of soil, cracks, or gulch in soil. Based on technical visits to the sites and the methodology used, seven risk areas in the city of Itambacuri were found. Were found in points 01 and 02, risk areas of type R4 (Very High Risk), in points 03 and 04, risk areas of type R3 (High Risk), and in points 05, 06, and 07, risk areas of type R2 (Medium Risk).